ДОСЛІДЖЕННЯ РЕЖИМІВ КОМПЕНСАЦІЇ РЕАКТИВНОЇ ПОТУЖНОСТІ В УЗАГАЛЬНЕНІЙ СИСТЕМІ ЕЛЕКТРОПОСТАЧАННЯ - Ягуп, В.Г.; Ягуп, К.В. (Інститут електродинаміки НАН України, Київ, 2022)
The article is devoted to the study of reactive power compensation modes //in a power supply system powered by a synchronous generator. This power remains in the system even after the application of transverse capacitor compensation, which is unable to provide full compensation of reactive power in the power supply system. Under these conditions, the optimal value of the parameter of the compensating capacitor was found on the computer model by the method of search optimization and the modes in the system with variations of the optimization criteria were investigated. References 16, figures 6.